Pemberdayaan UMKM Kain Sutera Corak Bunga Lagosi Berbasis Kearifan Lokal Dalam Meningkatkan Perekonomian - Andi Djemma, Siardin; Andi Yuniarti; Andi Nurwana; Akbar; Aliana; Intan Nurwana (Compile Journal of Society Service, 2025)
This community service activity aims to examine strategies for optimizing the empowerment of micro, small, and medium enterprises producing floral-patterned silk based on local wisdom principles to enhance the economy in Lagosi Village. The methods used involve observation, counseling, mentoring, and evaluation of implementation. This dedication contributes to a deeper understanding of how micro, small, and medium enterprises in palm sugar can play a role in sustainable development and the local economy. The implications of the policies generated from this research can assist the government and other stakeholders in supporting the empowerment of micro, small, and medium enterprises focused on local wisdom-based silk weaving, as well as improving the welfare of the local community.